An IoT Solution to Detect Overheated Idler Rollers in Belt Conveyors - Ibarra-Cabrera, Manuel J. (2026)
It is common knowledge that mechanical systems need oversight and maintenance procedures. There are numerous prevalent operation monitoring techniques, and in the era of IoT and predictive maintenance, it is possible to find multiple solutions to supervise these systems. This article describes the design and implementation of a low-cost system, which use an IoT approach to detect overheated idlers in conveyors belt in mining facilities. The system involves the use of temperature sensors, coordinately with heat map image sensors. The users (i.e., mining operators) can monitor overheated idlers in the whole conveyor belt, making on-demand queries using Telegram or a website, and also receiving autonomous warnings. Prototypes of this system were installed on a conveyor belt at a construction materials manufacturing company, and also in a copper mining company, both located in Apurimac, Peru. The usability and usefulness of the system were evaluated by 20 experts in maintenance and operation of conveyor belts, who filled the questionnaire proposed by TAM (Technology Acceptance Model). The results show that 91% of them consider the system useful for detecting the overheating of idlers in a conveyor belt, and 93% of them considers the solution as easy to use.